Legal Analysis of the Position of Personal Guarantee Owners in the Bank Credit Agreement Structure - Aslan Noor; Yeti Setiawati; Melliana Wijaya; Rohmani, Rodiah (Journal of Law, Politic and Humanities, 2024)
Bank loans play a vital role in supporting economic activities in Indonesia. One important instrument in managing credit risk is a personal guarantee, which involves a third party or the debtor himself to guarantee repayment of the loan in the event of default. This study analyzes the legal position of personal guarantees in the structure of bank credit agreements in Indonesia, identifying the effectiveness and risks associated with the use of personal guarantees. The normative juridical research method is used to explore conceptual and statutory approaches, and compare practices in the field. The results show that although personal guarantees provide an additional layer of security for banks, their utilization must be followed by an in-depth assessment of the guarantor's financial condition and the legal agreement made. Strict regulations and the application of prudential principles by banks are important to ensure that personal guarantees are effective in reducing credit risk, while supporting sustainable economic growth.